Factors affecting the performance of the head of the liang state government of salahutu district central maluku district - Fretes, Judy de; Latuconsina, Nurainy; Khairunissa, Atikah (International research journal of management, IT and social sciences, 2021)
The problem that occurs in the implementation of the state government is that the implementation of development policies has not been able to run optimally because of the state's change. Conflict in the head of the king's election, which has resulted in no country government heads being elected directly and becoming the definitive leader. Qualitative research methods are used to make direct observations in the field. The research results show that there is a lack of evaluation from the local government so that the problem of the emptiness of the king is not only in Liang Country but also in other customary countries in Central Maluku district. The implementation runs optimally because the head of state officials carrying out their duties properly and planning the country's development involves the community to participate actively.